Near-Infrared Switching of Light-Guided Random Laser - Sreekanth Perumbilavil; Martti Kauranen; Gaetano Assanto (IEEE Photonics Journal, 2018)
We report on all-optical modulation and switching of light-guided random laser emission in optically pumped dye-doped nematic liquid crystals, whereby a continuous-wave near-infrared beam at 1.064 μm, nonresonant with the medium and collinear with the pump source, forms a reorientational spatial soliton. Such soliton-assisted cavity-less laser exhibits a beam character with directional emission and smooth transverse profile and can be either switched-on or made more efficient by injecting a weak input. We achieve energy amplifications of laser emission in excess of 18 dB by injecting a 6 mW near-infrared beam.